Strategi Mahasiswa Universitas Negeri Medan dalam Meningkatkan Kemampuan Teknik Dasar Bulu Tangkis - Raswin; Mhd.Yan Ahady; Anggie Prisilia; Muhammad Yudha Pratama; Ferdi Hasan Lubis; Muhammad Hafis (Jurnal Nirta : Inovasi Multidisiplin, 2026)
This study aims to determine the strategies used by students to improve their basic technical skills in Bulu Tangkis at Universitas Negeri Medan. This research employed a qualitative approach with a field research design. The subjects of this study were students who actively participated in badminton activities on campus. Data collection techniques included observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The results showed that students applied several strategies to improve their basic badminton techniques, including regular practice individually or with peers, utilizing digital media to learn game techniques, participating in campus sports activities, and evaluating their playing performance. In addition, motivation, social support, and the availability of sports facilities also played an important role in improving students' basic badminton skills. Therefore, consistent training strategies and a supportive environment can help students improve their badminton playing skills effectively. Keywords: training strategies, basic techniques, badminton, students.